Gene therapy for disorders of sex development: current applications and future challenges - Peng, Wenyuan; Zhao, Qian; Chen, Jiali; Peng, Huifang; Jiang, Hongwei (Frontiers in Genetics, 2025)
Disorders of sex development (DSD) represent a spectrum of congenital conditions where discrepancies exist between chromosomal, gonadal, or anatomical sex. Recent advances in genomic diagnostics and gene-editing technologies have enabled significant progress in the identification of pathogenic variants and the exploration of targeted therapeutic strategies. This review systematically examines the roles of key sex-determining genes—including SRY, SOX9, NR5A1, WT1, FOXL2, and AR—in various DSD subtypes. It further elaborates on gene therapy strategies targeting these loci through the use of CRISPR/Cas9, TALENs, ZFNs, and viral vector-mediated delivery systems. Notably, CRISPR/Cas9 has been utilized to correct or epigenetically activate gene expression in vitro, such as SRY promoter demethylation in embryonic stem cells, and targeted disruption of SOX9 enhancers to model 46, XX testicular DSD in mice. Additionally, lentiviral vectors have enabled stable overexpression of transcriptional regulators (e.g., SOX9, NR5A1) in hiPSCs, inducing differentiation into Sertoli- and Leydig-like cells, with partial restoration of testicular function in vitro. Complementarily, AAV-based vectors—including AAV8 and synthetic AAVDJ—have demonstrated effective delivery of genes like Lhcgr into testicular interstitial tissues, restoring testosterone synthesis and fertility in mouse models. Despite this progress, current gene therapy approaches still face considerable technical challenges, such as off-target effects, immunogenicity of viral vectors or editing enzymes, and long-term transgene expression instability. Germline editing, while theoretically advantageous for early-onset DSD phenotypes, introduces profound ethical dilemmas due to its heritable nature. These include concerns regarding informed consent in minors, gender identity autonomy, and societal consequences of altering reproductive cells. Current international bioethics frameworks urge caution and recommend limiting clinical applications to somatic cells under stringent regulatory oversight. In conclusion, gene therapy offers a transformative potential for the diagnosis and treatment of DSD. Future directions should prioritize enhanced safety, precision delivery systems, and an ethically guided clinical translation pathway to ensure long-term efficacy and societal acceptability.